VARIASI GENETIK POPULASI Vanda foetida J.J.S. DI GUNUNG DEMPO DAN PADIAMPE, SUMATERA SELATAN BERDASARKAN KARAKTER MOLEKULAR - , DIAN ARUNI KUMALAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
It Vanda foetida J.J.S is an endemic orchid in Sumatra which first described in 1906 by J.J. Smith. was first found in Palembang, South Sumatra. Since described, V. foetida has not been seen in its habitat and the worldâs orchid collection until recent time. Thus, it is assumed that this species was taxonomically disappeared more than 100 years. The distribution of V. foetida was limited in the habitat because of the deep exploitation of this orchid. In 2010, V. foetida was found in Mount Dempo and Padiampe, South Sumatra. Coffee plantation and over-exploitation to fulfill commercial demand have become serious threats for V. foetida population that is now critically endangered. In-situ and ex-situ conservation patterns are needed to maintain the existence of V. foetida continuously. andom A The aim of this research was to study the genetic variation of V. foetida in its natural habitat, Mount Dempo and Padiampe, South Sumatra. Based on R mplified Polymorphic DNA (RAPD) analysis for genetic variation using 8 primers (OPU 3, OPU 5, OPU 6, OPU 7, OPU 12, OPU 13, OPU 14, and OPU 16), it is known that V. foetida originated from two populations were forming two main clusters in dendrogram with 67% (0,67) degree of similarity. Two populations of V. foetida at recent time were separated from larger population caused by habitat fragmentation. This phenomenon was showed by the grouping of individuals from both populations into one cluster in dendrogram. Two dendrogram clusters which showed low degree of similarity had revealed that the simpatric speciation occured in those populations. Genetic variation in each population was detected by the value of h (Neiâs genetic diversity) which results were 0,1999 and 0,1778 for Mount Dempo and Padiampe, respectively. The information of genetic variation can be used to support the V. foetida conservation, which mainly focussed on increasing the number of individuals and also enriching the genetic variation to maintain the existence of V. foetida populations.